Protein arginine methyltransferase 6 enhances immune checkpoint blockade efficacy via the STING pathway in MMR-proficient colorectal cancer - Tao Chen; Yu Zhang; Yang Sun; Ling Gao; Ting Lu; Jinlin Duan; Qiwei Li; Junyan Xue; Yonglong Zhang (Journal for ImmunoTherapy of Cancer)
Background The emergence of immunotherapy has revolutionized the paradigm of cancer treatment with immune checkpoint blockades (ICB) in solid cancers, including colorectal cancer (CRC). However, only a small subset of CRC patients harboring deficient mismatch repair (dMMR) or microsatellite instability-high (MSI-H) benefits from ICB therapy. A very limited response to ICB therapy has been achieved in MMR-proficient CRC, representing a significant challenge limiting the clinical application of immunotherapy. MMR is the critical DNA repair pathway that maintains genomic integrity by correcting DNA mismatches, which is mediated by the MutSα or MutSβ complex consisting of MSH2 with MSH6 and MSH3, respectively. Given that MMR status directs effective immune response, we sought to determine whether targeting MMR capacity boosts ICB efficacy.Methods Azoxymethane/dextran sodium sulfate (AOM/DSS)‐induced CRC and xenograft model were used to evaluate the function of PRMT6 and response to PRMT6 inhibitor EPZ020411 and combination therapy of PD1 and EPZ020411. Biochemical assays were performed to elucidate the underlying mechanism of PRMT6-mediated MSH2 methylation and immune evasion.Results We have identified PRMT6 as a crucial regulator of MMR capacity via MSH2 dimethylation at R171 and R219. Such a modification abrogates its MMR capacity and prevents the recruitment of MSH3 and MSH6. PRMT6 loss or inhibition triggers cytosolic DNA accumulation and cGAS-STING signaling activation, leading to enhanced immune response in PRMT6-deficient colon tumors or xenografts. Pharmacological inhibition of PRMT6 using EPZ020411 promotes mutagenesis and destabilizes MutSα or MutSβ assembly, and prolonged EPZ020411 exposure maintains an MSI-like phenotype in microsatellite stability (MSS) cells. EPZ020411 treatment sensitizes ICB efficacy of MSS cells, but not MSI cells in vivo. Similar effects have been observed in MSS colon tumors induced by AOM/DSS.Conclusions Our study provides a preclinical proof of concept to overcome resistance to immunotherapy by targeting PRMT6 in CRC with MSS.